Accessing the voices of children who use augmentative and alternative communication: Merits and pitfalls of co-construction - Smith, Martine (Peter Lang, 2018)
Children who have severe speech impairments and who rely on augmentative and alternative communication in order to express themselves are vulnerable to being silenced, due to their difficulties in producing communication others can understand. Because their speech is unintelligible, alternative modes of communication (e.g., picture boards, computer-based communication aids) are selected for them, often with minimal input from the child who is to use this form of communication. The vocabulary within the aid is selected by others and may align imperfectly with a child’s interest or motivation. In addition, children using aided communication may rely heavily on interaction partners to gloss and interpret their attempts at communication; it may be difficult for them to repair or challenge misinterpretations. This chapter explores the difficulties in accessing the voices of children with significant communication impairments and the potential opportunities to harness their input and views on the fundamental human activity of communication.
Seen and Heard: Exploring participation, engagement and voice for children with disabilities
Keywords: Children; Speech impairments; Aided communication; Misinterpretations; Interaction partners; Inclusive Society; ALTERNATIVE AND AUGMENTATIVE COMMUNICATION; CHILD LANGUAGE; Children; Communication; Relationships; Social participation